2014
DOI: 10.1021/am4044135
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Adhesion of Micropillars with Spatula Pads

Abstract: Natural gecko adhesive structures consisting of angled setae, branched into thin spatulas, have remarkable properties including easily attachable and releasable anisotropic adhesion. The geometrically asymmetric structures lead to anisotropic adhesive properties. Inspired by the gecko, we fabricated an array of micropillars with asymmetric spatula pads from elastomeric materials. This paper describes the anisotropic properties of the micropillars with spatula pads as established by experimental measurements an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Figure b,c indicates that the adhesive strength and response time can be varied depending on the structure and temperature of smart adhesive pad. The maximum adhesive strength (≈94 kPa) and adhesion switching ratio (≈293) at 61 °C of heating temperature are significantly higher than those of previous smart adhesive pads (see the comparison in Table S1, Supporting Information). In particular, in contrast to previous smart adhesive pads, our smart adhesive pads do not require any external preload to enhance the adhesion state.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Figure b,c indicates that the adhesive strength and response time can be varied depending on the structure and temperature of smart adhesive pad. The maximum adhesive strength (≈94 kPa) and adhesion switching ratio (≈293) at 61 °C of heating temperature are significantly higher than those of previous smart adhesive pads (see the comparison in Table S1, Supporting Information). In particular, in contrast to previous smart adhesive pads, our smart adhesive pads do not require any external preload to enhance the adhesion state.…”
mentioning
confidence: 68%
“…However, most of the previous artificial adhesive systems do not provide a high on/off adhesive strength ratio (i.e., the ratio of the adhesive strengths in the high‐/low‐adhesion states) with excellent switchability. In particular, reversible adhesion with a high on/off switching ratio in a wet environment has rarely been demonstrated (refer to Table S1 in the Supporting Information for the comparison of reversible adhesion properties).…”
mentioning
confidence: 99%
“…The study found that there was reduced adhesion of E. coli cells to the pillared surface compared to a flat surface [ 15 ]. NIL has also been used to produce nano-structures on indium phosphate, gallium phosphate and silicon substrates [ 13 , 67 ], and to prepare micro-pillar patterned surfaces, inspired by gecko setae [ 68 ].…”
Section: Artificial Surface Fabricationmentioning
confidence: 99%
“…Moreover, the mushroom-shaped tip can insert certain vacuum pressure during the pull-off, enlarging the adhesion forces [109,110]. If the overhang is not symmetric, like the spatula-shaped tip, anisotropy adhesion can be obtained [111,112,113]. The pillar with the stepped mushroom-shaped tip offers different contact areas in opposite directions, and the ratio of adhesion strength obtained in different directions exceeds 20 [71].…”
Section: Bioinspired Hierarchical Structured Adhesivesmentioning
confidence: 99%